THU0242 Pregnancy outcomes and disease activity in women with axial spondyloarthritis: a systematic literature review. (12th June 2018) - Moltó, A.; Gensler, L.; Clowse, M.E.B.; Marzo-Ortega, H.; Artignan, A.; Goff-Leggett, D.; Leonard, S.; Resemann, H.K.; Thurtle, E.; de Peyrecave, N.; Ecoffet, C.; Förger, F.
Abstract : Background: Women with axial spondyloarthritis (axSpA) are often affected by the disease during their reproductive years, 1 but reports on disease activity and pregnancy outcomes in these patients (pts) are sparse. In women with ankylosing spondylitis (AS), also currently termed as radiographic axSpA, a higher risk of disease activity flares and prevalence of adverse pregnancy outcomes have been reported vs healthy controls; however, in non-radiographic (nr)-axSpA pts, such data are virtually non-existent. 2, 3 Objectives: To review the available evidence on the relationship between axSpA disease activity and pregnancy, including foetal outcomes. Methods: A systematic literature review was conducted in October 2017 by searching EMBASE, MEDLINE ®, the Cochrane Database of Systematic Reviews, and the Database of Abstracts of Reviews of Effects. Publications were systematically screened for English language articles on observational studies of axSpA pts reporting pregnancy outcomes or disease activity during pregnancy. Studies utilising agents contraindicated in pregnancy were excluded. Supplementary searches of selected, 2016–17 conference proceedings and bibliographies of relevant review articles were also conducted. Results: 2216 publications were reviewed, with 20 publications on 15 unique studies meeting the inclusion criteria. When utilising the verified disease activity measurement instruments, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) or Ankylosing Spondylitis Disease Activity Score C-Reactive Protein (ASDAS-CRP), 5 studies (3 prospective, 2 retrospective) reported active disease (as described by individual studies; table 1) both during pregnancy and postpartum in most pts. Pregnancy outcomes in axSpA pts were compared with healthy controls in 6 studies (3 retrospective, 2 prospective, 1 case-control), the 3 largest of which (including 1 prospective) revealed higher risk or odds of preterm births in axSpA pts. Higher rates or risk of low birth weight/small-for-gestational-age neonates were shown in pts vs controls in 2/5 studies reporting such outcomes. Stillbirths, miscarriages or foetal loss/abortion were found to occur at similar rates in both populations. Conclusions: Robust, prospective data on disease activity during pregnancies of women with axSpA are limited. Within the samples reported here, available data suggest that there may be a small increase in pre-term births; no signal for increased pregnancy loss was detected. Further research is needed to investigate relationships between maternal disease activity and pregnancy outcomes in axSpA. References: [1] van den Brandt S. Arthritis Res Ther2017;19(1):64. [2] Jethwa H. Arthritis Rheumatol2016;68(suppl 10). [3] Jakobsson GL. Ann Rheum Dis2016;75(10):1838–42. Acknowledgements: This study was funded by UCB Pharma. Editorial services were provided by Costello Medical. Disclosure of Interest: A. Moltó Grant/research support from: MSD, AbbVie, Pfizer, UCB Pharma, Consultant for: MSD, AbbVie, Pfizer, UCB Pharma, L. Gensler Grant/research support from: UCB Pharma, M. Clowse Grant/research support from: AbbVie, Bristol-Myers Squibb, Janssen, Pfizer, Consultant for: Pfizer, Janssen, UCB Pharma, H. Marzo-Ortega Grant/research support from: Janssen, Speakers bureau: Abbvie, Celgene, Janssen, MSD, Novartis, Pfizer, UCB Pharma, A. Artignan Employee of: Costello Medical, D. Goff-Leggett Employee of: Costello Medical, S. Leonard Employee of: Costello Medical, H. Resemann Employee of: Costello Medical, E. Thurtle Employee of: Costello Medical, N. de Peyrecave Employee of: UCB Pharma, C. Ecoffet Employee of: UCB Pharma, F. Förger Grant/research support from: UCB Pharma, Speakers bureau: Mepha, Roche, UCB Pharma